Serum granzyme B is associated with otorhinolaryngological, pulmonary, and renal involvement of antineutrophil cytoplasmic antibody-associated vasculitis. (January 2021) - Yoon, Taejun; Yoo, Juyoung; Ahn, Sung Soo; Song, Jason Jungsik; Park, Yong-Beom; Lee, Sang-Won
We investigated whether serum granzyme B (GrB) can reflect the inflammatory burden such as cross-sectional disease activity and organ-specific involvement in immunosuppressive drug-naïve patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Seventy-eight immunosuppressive drug-naïve patients with AAV were included in this study. At the time of the first classification, whole blood was obtained from each patient and sera was immediately isolated and stored at – 80°C. On the day of the blood sampling, we performed routine laboratory tests including antineutrophil cytoplasmic antibody tests and collected both clinical and laboratory data. AAV-specific indices included Birmingham Vasculitis Activity Score (BVAS) and Five-Factor Score (FFS). The median age of patients with AAV was 62 years and 26 patients were men. Serum GrB was not associated with the cross-sectional BVAS; however, patients with serum GrB positivity exhibited higher frequencies of otorhinolaryngological manifestation than those without (p=0.037). When serum GrB levels were compared after dividing the patients into two groups based on the presence of organ-specific involvement, patients with pulmonary involvement exhibited a significantly higher serum GrB than those without (p=0.042). On the other hand, patients with renal involvement showed a significantly lower serum GrB than those without (p=0.023). In addition, serum GrB was inversely correlated with the cross-sectional FFS (r=−0.249, p=0.028). Even though serum GrB could not reflect the inflammatory burden of AAV, serum GrB was associated with otorhinolaryngological, pulmonary, and renal involvement in immunosuppressive drug-naïve patients with AAV.